Development of waste management planning for the construction sector considering cycle economy - Eleftheriou, Eleftherios; Tantele, Elia; Votsis, Renos; Charilaou, Eleni (My University, 2020)
Waste is an area regulated by a large number of legislations at both international and European Union level. Building waste was recognized as a special waste stream in the 1990s and identified as a priority waste stream. This recognition for this waste stream was necessary because of the large proportion of this waste in proportion to the total amount of waste, but also the huge potential for reuse and recycling contained. The term used in Cyprus Legislation is Excavation, Construction and Demolition Waste, which includes waste from the construction and civil engineering works, and of natural and technological disasters. The aforementioned waste is also produced by the demolition of existing buildings as well as from renovation and maintenance work. They contain various ingredients-hazardous or not, and problems arise when their management doesn’t take into account the protection of the environment and public health. This paper deals with the management of Construction and Demolition Waste considering the Cycle economy, with a special focus on Cyprus, as well as the analysis of the existing strategy and policy on the national level. On this basis, solutions are proposed, and recommendations are noted where needed as to revising, updating and strengthening the existing policy.
Keywords: Construction waste management; European Union; Strategy; Sustainable development; SWOT analysis